ChemInform Abstract: Chemical Modification in the Design of Immobilized Enzyme Biocatalysts: Drawbacks and Opportunities. Issue 33 (July 2016) - Rueda, Nazzoly; dos Santos, Jose C. S.; Ortiz, Claudia; Torres, Rodrigo; Barbosa, Oveimar; Rodrigues, Rafael C.; Berenguer‐Murcia, Angel; Fernandez‐Lafuente, Roberto
Abstract: Review: [82 refs.